Distinct TP53 Mutation Subtypes Differentially Influence Cellular Iron Metabolism - Stephen L. Clarke (Nutrients, 2019)
The most commonly mutated gene in all human cancers is the tumor suppressor gene TP53; however, in addition to the loss of tumor suppressor functions, mutations in TP53 can also promote cancer progression by altering cellular iron acquisition and metabolism. The primary objective of this work was to determine how TP53 mutation status influences the molecular control of iron homeostasis. The effect of TP53 mutation type on cellular iron homeostasis was examined using cell lines with inducible versions of either wild-type TP53 or a representative mutated TP53 gene from exemplary “hotspot” mutations in the DNA binding domain (R248, R273, and R175) as well as H193Y. The introduction of distinct TP53 mutation types alone was sufficient to disrupt cellular iron metabolism. These effects were mediated, at least in part, due to differences in the responsiveness of iron regulatory proteins (IRPs) to cellular iron availability. IRPs are considered the master regulators of intracellular iron homeostasis because they coordinate the expression of iron storage (ferritin) and iron uptake (transferrin receptor) genes. In response to changes in iron availability, cells harboring either a wild-type TP53 or R273H TP53 mutation displayed canonical IRP-mediated responses, but neither IRP1 RNA binding activity nor IRP2 protein levels were affected by changes in iron status in cells harboring the R175H mutation type. However, all mutation types exhibited robust changes in ferritin and transferrin receptor protein expression in response to iron loading and iron chelation, respectively. These findings suggest a novel, IRP-independent mode of iron regulation in cells expressing distinct TP53 mutations. As TP53 is mutated in nearly half of all human cancers, and iron is necessary for cancer cell growth and proliferation, the studies have implications for a wide range of clinically important cancers.